Knowledge and education in classical Islam: religious learning between continuity and change / Volume 2 - Günther, Sebastian (Knowledge and education in classical Islam religious learning between continuity and change, 2020)
Volume 2. Part VI. Travel, the Exact Sciences, and Islamic Learning: 24. War and Travel, Patrons and the Mail: The Education of Abū l-Rayḥān al-Bīrūnī (d. 440/1048) / Barbara Stowasser -- 25. Variants of Galenism: Ibn Hindū and Ibn Riḍwān on the Study of Medicine / Lutz Richter-Bernburg -- 26. Teaching Mathematical and Astronomical Knowledge in Classical and Post-Classical Islamicate Societies / Sonja Brentjes -- Part VII. Politics of Knowledge and Muslim Identity: 27. The Development of a Sufi Anti-curriculum: Politics of Knowledge and Authority in Classical Islamic Education / Sara Abdel-Latif -- 28. Knowledge in the Buyid Period: Practices and Formation of Social Identity / Nuha Alshaar -- 29. A Ruler's Curriculum: Transcultural Comparisons of Mirrors for Princes / Enrico Boccaccini --30. Interpretive Power and Conflicts of Interpretive Power: Caliphate, Religion, and "True" Islamic Education at the Dawn of the Seventh/Thirteenth Century in Baghdad / Angelika Hartmann -- 31. The ʻĀlim-Caliph: Reimagining the Caliph as a Man of Learning in Eighth/Fourteenth and Ninth/Fifteenth-Century Egypt / Mustafa Banister -- Part VIII. Principles and Practices in Ibadi and Shiʻi Learning: 32. Teaching Ethics in Early Ibadism: A Preliminary Study / Jana Newiger -- 33. Scholars of Ḥilla and the Early Imami Legal Tradition: Ibn Abī ʻAqīl and Ibn al-Junayd, "The Two Ancient Scholars," Retrieved / Ali R. Rizek -- 34. Shiʻi Higher Learning in the Pre-Safavid Period: Scholars, Educational Ideals, Practices, and Curricula / Maryam Moazzen -- Part IX. Gender, Human Growth, and Authority in Muslim Education -- 35. Denial of Similitude: The Exegetical Concern with Gender in "And the Male Is Not Like the Female" (Q3:36) / Hosn Abboud --36. "If Music Be the Food of Love?" The Singing-Girls and the Notion of Ṭarab as Part of an Adab-Ideal / Agnes Imhof -- 37. Women Scholars of Ḥadīth: A Case Study of the Eighth/Fourteenth-Century Muʻjam al-Shaykha Maryam / Mohsen Haredy -- 38. Knowledge, Piety, and Religious Leadership in the Late Middle Ages: Reinstating Women in the Master Narrative / Asma Afsaruddin -- Part X. Transformations of Classical Muslim Learning: 39. The Development of Arabo-Islamic Education among Members of the Mamluk Military / Christian Mauder -- 40. Dissociation of Theology from Philosophy in the Late Ottoman Period / Mehmet Kalaycı -- 41. The Malaysian Scholar Syed Muhammad Naquib al-Attas (b.1931) on Islamic Education: An Evaluation in View of Classical Islamic Sources / HansDaiber -- General Notes on the Indices -- Index of Proper Names -- Index of Geographical Names and Toponyms -- Index of Book Titles and Other Texts -- Index of Scriptural References -- Ḥadīth Index --Index of Topics and Keywords.